Evaluation of the Effects of using Central Pattern Generators to Synchronize the Undulating Motion of a Bio-Inspired Robotic Fin Testbed (LACCEI, 2024)
Unmanned Underwater Vehicles (UUVs) with bio-inspired fin propulsion systems have captivated the interest of many researchers in recent years, particularly because such systems provide higher dexterity and energy efficiency, and less environment perturbation when compared to conventional propeller-based propulsion. Bio-inspired propulsion UUVs designs are typically based on large chains of articulated actuators, which must be properly synchronized to achieve the desired UUV gait motion. To achieve this task, a control strategy based on artificial Central Pattern Generators (CPGs) is commonly used. CPGs provide a highly stable, smooth, synchronized controlled transition of a large number of individually driven actuators, but solving the dynamic equations of the CPG model results in an increase in the computing requirements of the UUV microcontroller, which may limit its implementation on UUVs with a high number of actuators and microcontroller with limited computing power. Thus, the purpose of this work is to evaluate the feasibility and limitations of implementing a CPG-based locomotion control strategy on an Arduino® Mega microcontroller to drive a 16-actuator articulated testbed of an undulating robotic fin, as well as the dynamic effects of the CPG control strategy. The results demonstrate that a CPG can be implemented on the Arduino® Mega platform by optimizing the structure of the CPG equations while still maintaining the favorable qualities of CPG-based control when compared to a direct undulating wave-based control approach.